Modification of magnetic nanoparticle lipase designs for biodiesel production from palm oil - Raita, Marisa; Arnthong, Jantima; Champreda, Verawat; Laosiripojana, Navadol (Fuel processing technology, 2015)
Biocatalytic conversion of vegetable oils by immobilized lipase to fatty acid methyl ester (FAME) is an efficient eco-friendly alternative to the conventional alkaline-catalyzed biodiesel production process. In this work, immobilization of Thermomyces lanuginosus lipase on Fe sub(3)O sub(4) was studied using different covalent linkage designs. Immobilization of lipase on magnetic supports was shown by Fourier-Transformed infrared microscopy and scanning electron microscopy. Immobilized lipase prepared on Fe sub(3)O sub(4) carrier modified by 3-aminopropyl triethyoxysilane and covalently linked by 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide (Fe sub(3)O sub(4)-AP-EN-LIP) showed the highest catalytic activity on hydrolysis of p-nitrophenyl palmitate and transesterification of refined palm oil. Reaction variables were optimized by Central Composite Design, which identified 23.2% w/w enzyme loading and 4.7:1 methanol to FFAs molar ratio with 3.4% water content in the presence of 1:1 (v/v) tert-butanol to oil as optimal conditions, leading to 97.2% FAME yield after incubation at 50 [degrees]C for 24 h. The biocatalyst showed high operational stability and could be simply separated by magnetization and recycled for at least 5 consecutive batches with > 80% activity remaining, suggesting its potential for application in biocatalytic biodiesel synthesis.